Conhecimento e conduta de neonatologistas de um hospital universitário sobre saúde auditiva - Rafael Neto, José (2021)
Objective: To investigate the knowledge and behavior of neonatologists at a university hospital about children's hearing health. Method: Descriptive and exploratory research, with a quantitative approach, developed with eight neonatologists who work in the maternity and Neonatal ICU sectors of a University Hospital from April to June 2021. Results: The neonatologists reported not having specific training courses in the area of hearing health/hearing impairment, all reported that the knowledge they have in the area was obtained in the undergraduate course of Medicine. Regarding the conduct adopted at the time of hospital discharge when the child fails the screening, three neonatologists reported guiding the family to perform speech therapy, two indicate a retest and three indicate a retest including the performance of the ABR in addition to the otoacoustic emissions test . About the ideal period for a child with hearing loss to start using an electronic hearing device, four responded 6 months of age, one responded 1 year old, one responded 2 years old and two responded 6 years old. Conclusion: it can be concluded that most neonatologists have knowledge about child hearing health, but they are limited in relation to the unfolding of the stages of neonatal hearing screening, as well as the actions and processes of intervention in hearing loss and monitoring of the newborns.